"Plan de Proyecto para Desarrollo de El Albergue de Montaña El Roble" - Alfaro-Víquez, Carlos; Brenes-Torres, Eduardo (Instituto Tecnológico de Costa Rica, 2011)
Breneto S.A. is a society which owns a piece of land of 17 hectares in Cartago. The board is interested in developing a tourism project in the area; it will be like a small mountain hotel. It is required a feasibility investigation at profile level. Also it is required a project plan, including the Initiating and Planning phases from the PMBOK, The financial results from the feasibility investigation show the following numbers. The more realistic scenario has NPV $36,309, IRR 13,52% and RP 3,19 years. The pessimistic scenario with a supposed reduction of 10% in income has NPV - $24,761, IRR 0,59% and RP3,47. The optimistic scenario with a supposed increase of 10% in income has NPV $97,378, IRR 25,85% and RP 2,91 years. The project plan includes the Initiation and planning processes based in the best practices mentioned in the PMBOK, taking in consideration the nine areas of knowledge. These areas are: Scope, Time, Cost, Quality, Human Resources Communication, Acquisitions and Risks. Every area needs a plan. It is recommended to elaborate a full feasibly investigation to assure the profitability indicated in the profile-level investigation. It is also important to get support from organizations like ICT and CANATUR which are experts in tourism management. It should be follow the project plan to reduce the deviations in costs, time and quality, and to meet the client expectations.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2011.
Keywords: Factibilidad; Turismo ecológico; Oferta y demanda; Gestión ambiental; Gestión del tiempo; Costos; Comunicación; Riesgos